Study on the Effect of Isotropic Initial Stress on the Anchoring Performance of Self-Expanding Bolts - Jie Liu; Hongya Li; Yunzhou Li; Yunan Yang; Tao Sun; Rui Song; Rongqi Sun (Advances in Civil Engineering)
In order to study the anchoring performance of a new type of self-expanding, high-strength, precompression anchoring technology with a large amount of expansion agent (ω ≥ 5) cement slurry as anchoring solids under confined surrounding rock conditions, a rock mass anchoring device and methods that simulate in situ stress are developed, and real-time monitoring of expansion stress and anchor pull-out tests are carried out. The results show that the internal interface stress has a loss effect over time, and the stress loss value shows a linear increase trend with the dosage, but the loss rate shows a linear decreasing relationship with the dosage. This paper defines the coordinated additional stress and obtains its temporal and spatial evolution law in the rock mass. It is pointed out that there is a lag time difference between the peak of internal interface stress and the peak of coordinated additional stress, explaining its mechanical mechanism from the perspective of stress transfer. The strong restraint of the sealing section of the anchor hole causes the anchor solid to form a “shuttle-shaped” microexpanded head with thin ends and a middle drum under the expansion stress. During the drawing process, the microexpanded head is “stuck” in the anchor hole and moves upward to form the unique “load platform effect” of the anchoring system. And the mechanical mechanism diagram of this effect is obtained. It is pointed out that this effect can greatly improve the ductility of the anchoring system and the ultimate energy consumption value of damage. A prediction model for the ultimate pull-out force of self-expanding bolts is established. It is pointed out that the initial confining stress value has an exponential effect on the ultimate pull-out force. It shows that the surrounding rock with strong confinement constraints can greatly increase the ultimate pull-out resistance of the bolt. The self-expanding strengthening coefficient λ and the surrounding rock stress influence coefficient k are introduced, the bolt interface mechanics formula and energy equation of the self-expanding anchor system are established, and the feasibility of the formula is verified by the calculation example. It is concluded that the ultimate pull-out resistance of the anchorage with ω = 30 is increased by 3.38 times compared with the ordinary anchorage under the initial confining stress condition of 0.7 MPa, the prepeak displacement of the bolt is increased by 2.08 times, and the prepeak energy consumption of the anchoring system is increased by 7.34 times. The cost only increased by 0.023% based on the literature example.